Amplified Fragment Length Polymorphism Mapping of Tomato Backcross Populations - Ojha, B.R. (Journal of the Institute of Agriculture and Animal Science, 2003)
Tomato backcross populations of Lycopersicon exculentum cv. Money Maker x Lycopersicon pennellii LA716 were used for construction of an Amplified Fragment Length Polymorphism (AELP) map based on pennellii markers. Ten primer combinations (7 of Eco-Mse and 3 of Pst-Mse) were used. This map spanned 893.7 cM and contained 187 AFLP markers, consisting 130 previously found markers and 57 new markers. A total of 141 markers were found from Eco-Mse primer combination and 46 from Pst-Mse primer combination. The Eco-Mse AFLP markers were not evenly distributed over the chromosomes. The Pst-Mse AFLP markers were found quite frequently and evenly distributed in the more distal part of the chromosomes. Eco-Mse markers were found quite more in numbers in chromosomes 5 and 9, whereas Pst-Mse markers in chromosomes 1 and 7. In chromosomes 4, 6, 7 and 8, the new markers and previously found markers were found quite equal in numbers. The average number of informative markers per primer combination was 18.7 ranging from 6 (E33M47) to 36(E35M48). The average size of map per chromosome was found 74.5 cM ranging from 46.2 cM of chromosome 8 and 105.5 cm of chromosome 3. Fourteen BC1 plants for BC2 and subsequently 12 BC2 plants for BC3 generation were selected to obtain inbred lines with genes of interest. BC1 plants were selected each representing about 50% Lycopersicon pennellii LA716 genome and BC2 plants were selected each representing about 25% genome coverage, and together cover 100% of the Lycopersicon pennellii genome based on scored markers J. Inst. Agric. Anim. Sci. 2003 24:21-28.